(untitled) (UNED Research Journal, 2017)
Tuna and shark are the main fish in which analysis of mercury content are made in Costa Rica. The main destinations are domestic consumption, import and export, in that order. On these analyzes a simple statistical evaluation was performed to estimate the values of weekly intake recommended for risk groups according to FAO. Records analysis by the Laboratorio Nacional de Servicios Veterinarios (LANASEVE) were used, considering the information related to type of fish, lot size, destination and mercury concentration. Lots were analyzed statistically in a range between 500 and 100.000 kg, where 439 data were available for tuna and 421 for shark. The lots are concentrated in the range between 1000 and 100,000 kg, with variations depending on species. The percentages above the legal limit of 1,00 mg Hg * kg-1 of fish are 7.1% for tuna and 20.7% shark. The populations of tuna and shark are not comparable, while the average of the different destinations tuna are more homogeneous than the shark. Data concentration of mercury in fish have a type Poisson distribution, with mean values of 0,577 mg Hg / kg of tuna and 0,860 mg Hg / kg of shark. These values are similar to those of other studies for these types of fish.